PERBEDAAN KEBOCORAN MIKRO RESTORASI RESIN KOMPOSIT SELF ADHESIVE DENGAN FLOWABLE BONDING SELF ETCH PADA TEPI GINGIVAL DAN OKLUSAL KAVITAS ABRASI SERVIKAL - , Kristanti Yarmastuti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this study was to investigate the microleakage differences of self-adhesive flowable and flowable resin composite with one step of self-etch bonding either at gingival margin or occlusal margin in servical lesions. Twenty eight caries free maxillary premolar teeth were prepared to create wedge shape on both buccal and palatal side. The dimension of cavity preparation was wedge shape (2 mm in depth and 3 mm in width of gingivo-occlusal direction). The gingival margin was within apically of cemento-enamel junction, with ending at cementum./dentin. The occlusal margin was within coronally of cemento-enamel junction, with ending at enamel. All teeth were randomly assigned into two groups of 14 each. First group was restored with self-adhesive flowable, and the second group was restored with flowable bonding self-etch. Following immersion in artificial saliva for 24 hour at a temperature of 370 C, the teeth were thermocycled (40 C and 550 C each of 1 minute), and were immersed in 2% methylene blue solution. All teeth were sectioned in bucco-palatal direction and the depth of penetration was scored (0-3). Data obtained were analyzed using Mann-Whitney U test with level of significance=0,05. The statistical analysis revealed that a significant difference occurred at each group, group I restored with self adhesive flowable and group II restored with flowable with one step self etch bonding (p gingival 0,014 and p occlusal 0,048). There is a significant difference for gingival margin and occlusal margin in group II which restored with flowable one step self etch bonding (p=0,043) and no significant difference for gingival margin and occlusal margin in group I which restored with self-adhesive flowable (p=0,092). It can be concluded that there is a different microleakage of resin composite using self- adhesive flowable and flowable resin composite with one step self-etch bonding. There is a diiferent microleakage of gingival margin and occlusal margin in the second group. There is no different microleakage of gingival margin and occlusal margin in the first group.